Energy Consumption and Economic Growth: Evidence from Vietnam - Nguyen, Ha Minh; Bui, Ngoc Hoang; Vo, Duc Hong; McAleer, Michael (Journal of Reviews on Global Economics, 2019)
The importance of non-renewable, renewable and sustainable energy sources and energy consumption in the economic development strategy of a country is undeniable. The purpose of the paper is to investigate the impacts of energy consumption on the economic growth of Vietnam during the 1980-2014 period. By applying the Autoregressive Distributed Lag (ARDL) model of Pesaran et al. (2001), and the Granger causality test of Toda and Yamamoto (1995), the empirical results provide evidence that electricity consumption has positive impacts on Vietnam's economic growth in both the short run and long run. For public policy prescriptions, the empirical evidence suggests that an exploration of new sources of renewable and sustainable energy is essential for long run economic development.